Diabetes and Tooth Loss among Working-Age African Americans: A National Perspective - Hastings, Julia F. (Soc Work Public Health, 2017)
Natural teeth are still lost in adults despite improvements in dental care and access to treatment across the life span. The study examined whether tooth loss can be mitigated in adults experiencing diabetes. National online survey data from the Service Utilization among African Americans with Co-morbid Depression and Diabetes (n = 275) were analyzed using logistic regression analyses. Diabetes was most prevalent among men (73.5%) and least prevalent among women (40.6%). In general and among the women, those without diabetes have approximately 50% fewer missing teeth than those with diabetes (odds ratio = .50; 95% confidence interval: 0.30, 0.83). Tooth loss is a traumatic experience and a serious life event that requires professional attention.